Factors associated with compliance in implementing health protocols to prevent COVID-19 in Indonesia: A cross-sectional study - Ambar Erawati (Jurnal Ners, 2022)
Introduction: To prevent the COVID-19 spread, the government requires people to comply with health protocols in public facilities, namely by wearing masks, washing hands and keeping a distance. This study aimed to determine what factors affect and reason for compliance in implementing health protocols. Methods: This research was an analytical survey research with a cross-sectional design conducted in Semarang City, Indonesia, with a total sample of 400 respondents. The independent variables were age, education, occupation, and health status. The dependent variable was compliance in wearing masks, washing hands and keeping a distance. Data were analysed with logistic regression test with significance level of 0.05. Results: From the survey, 76.6% of respondents obeyed wearing masks, 57.4% of respondents obeyed to wash their hands and 71.1% of respondents obeyed to keep their distance. The backward type logistic regression test found that the factors associated with health protocol compliance were age, education, occupation, health status, existing regulations and the desire to maintain health with a significance value of <0.001. However, field of work was not associated with using masks (p = 0.273), while health status was not associated with handwashing habits (p = 0.344). Conclusions: Factors that are associated with respondents' compliance with the health protocol are age, education, occupation, health status, self-motivation and regulation. The government need to raise awareness on adhering health protocols through the promotion about healthy lifestyle.